2021
DOI: 10.1002/celc.202001517
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Generation from Water‐Annealed TiO2 Nanotubes with White and Grey Modification

Abstract: In recent years, photocatalytic reactions on anodic TiO2 nanotubes have been intensively investigated. In order to show photocatalytic activity, anodically formed nanotubes need to be crystallized to anatase. This is conventionally done by thermal annealing in air at temperatures 400–600 °C. Recently, a so‐called “water annealing” treatment has been reported to be effective to also create a highly active form for photocatalysis. Here we report on the feasibility of using a water annealing treatment of TiO2 nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…[ 1–5 ] Hydrogen (H 2 ) is considered to be one of the most hopeful candidate to replace fossil energy because of its higher energy density and only water as by‐product during combustion process. [ 6–8 ] Among multitudinous H 2 production strategies, solar‐driven hydrogen generation from water via semiconductor photocatalyst has been deliberated as a potential technology for sustainable hydrogen production. [ 9–15 ] It is known that the core and key of solar‐driven H 2 generation technology are the photocatalysts used in the photocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] Hydrogen (H 2 ) is considered to be one of the most hopeful candidate to replace fossil energy because of its higher energy density and only water as by‐product during combustion process. [ 6–8 ] Among multitudinous H 2 production strategies, solar‐driven hydrogen generation from water via semiconductor photocatalyst has been deliberated as a potential technology for sustainable hydrogen production. [ 9–15 ] It is known that the core and key of solar‐driven H 2 generation technology are the photocatalysts used in the photocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the grey titania nanostructures yield stable photocatalytic performance in the absence of noble metals; the photoactivation was ascribed to the formation of surface defect states such as oxygen vacancies and trivalent titanium ions (Ti 3+ ) [31]. These defect states can act as intrinsic co-catalytic centers to promote photocatalysis [32]. Furthermore, the heterophase junction between anatase and rutile improves the transfer of photoinduced electrons at the anatase-rutile interface and boosts the charge separation, leading to higher photocatalytic activity [4].…”
Section: Introductionmentioning
confidence: 99%
“…For this, we use so-called grey TiO 2 , produced by annealing commercial anatase nanopowders in hydrogen atmosphere (see also SI). [44,45] This material facilitates electron and hole transfer to aqueous solutions [44,[46][47][48] -this feature is crucial for an efficient oxidation of graphite in an aqueous solution. The approach presented here to photocatalytically oxidize graphite using grey TiO 2 and UV light without other designated electron or hole capture agents, in fact, provides a one-step synthesis of TiO 2 -GO composites with adjustable properties.…”
Section: Resultsmentioning
confidence: 99%